Mean-median compromise method as an innovating voting rule in social choice theory - Ngoie, Ruffin-Benoit; Ulungu E-L, Berthold (International Journal of Applied Mathematical Research, 2015)
This paper aims at presenting a new voting function which is obtained in Balinski-Laraki’s framework and benefits mean and median advantages. The so-called Mean-Median Comprise Method (MMCM) has fulfilled criteria such as unanimity, neutrality, anonymity, monotonicity, and Arrow’s independence of irrelevant alternatives. It also generalizes approval voting system.